Precision Therapy for a Chinese Family With Maturity-Onset Diabetes of the Young - Li, Juyi; Shu, Meng; Wang, Xiufang; Deng, Aiping; Wen, Chong; Wang, Juanjuan; Jin, Si; Zhang, Hongmei (Frontiers in Endocrinology, 2021)
Abstract Objective To determine the pathogenic gene and explore the clinical characteristics of maturity-onset diabetes of the young type 2 (MODY2) pedigree caused by a glucokinase (GCK) gene mutation. Methods Using whole-exome sequencing (WES), we detected the pathogenic gene in the proband—A 20-year-old young man who was accidentally found hyperglycemia, no ketosis tendency, and a family history of diabetes. The family members were investigated to collect relevant clinical data and obtain peripheral blood genomic DNA of them. The candidate pathologic variants were verified by Sanger sequencing technology, and cosegregation tests were conducted among other family members and nonrelated healthy controls. After adjusting the treatment plan according to the results of genetic testing, observe the changes of biochemical parameters such as blood glucose levels and HAblc levels. Results A heterozygous missense mutation c.1160C > T (p.Ala387Val) in exon 9 of GCK gene (NM_000162) was found in the proband, his father, uncle and grandmother—which is cosegregated with diabetes. It is the first discovery in the Asian population. After stopping hypoglycemic drug treatment, good glycemic control continued with diet and exercise therapy. Conclusion GCK gene mutation c.1160C > T (p.Ala387Val) is the pathogenic gene in the GCK-MODY pedigree. Formulating a reasonable and personalized treatment strategy can reduce unnecessary excessive medical treatment and adverse drug reactions, and obtain a good HbA1c compliance rate Keywords: Glucokinase (GCK); Monogenic diabetes; Mutation; MODY2; pedigree; Chinese